Evaluation of Tuberculosis Control Strategy and Challenges in Indonesia After Pandemic COVID-19 - Meutya Zahra Eriansyah,; Anggraeni Dian Ciptaningrum,; Afifah Thaliah Putri Priyono,; Almeria Annisa Putri,; Riswandy Wasir, (International Journal Of Health Science, 2025)
Prior to the COVID-19 pandemic, Indonesia had made measured progress in addressing its tuberculosis (TB) burden through national strategies such as DOTS and integration into the universal health coverage (UHC) system. However, the pandemic caused substantial disruption to TB control efforts, including declines in case detection, treatment coverage, and continuity of care. This literature review analyzed eight peer-reviewed articles published between 2020 and 2025, selected from the Google Scholar database, to assess post-pandemic TB control strategies and challenges in Indonesia. The findings indicate that digital platforms were increasingly utilized for TB screening, monitoring, and reporting, while community-based education and expanded partnerships with private providers were promoted to maintain service continuity. Despite these adaptations, challenges such as limited infrastructure, inadequate digital literacy, constrained resources, and persistent stigma remain significant barriers. Strengthening the health system’s capacity, improving policy coherence between TB programs and insurance schemes, and sustaining innovation through multisectoral collaboration are essential to rebuilding TB services and advancing toward national and global TB elimination goals.